2021
DOI: 10.1128/msphere.00575-21
|View full text |Cite
|
Sign up to set email alerts
|

MCR-5-Producing Colistin-Resistant Cupriavidus gilardii Strain from Well Water in Batna, Algeria

Abstract: Colistin resistance mediated by mcr genes in Gram-negative bacteria has gained significant attention worldwide. This is due to the ability of these genes to be horizontally transferred between different bacterial genera and species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…followed by unclassified members of Xanthomonadales, Dokdonella, Pseudomonas, and Hydrogenophilales. Although many of the potential mcr- 5 host identified in this study have not been associated with this variant, it has been observed in Stenotrophomonas isolated from poultry farm waste and Cupriavidus isolated from a clinical case and well water. , Both Stenotrophomonas and Cupriavidus genera contain species that are considered emerging global pathogens while others, such as species within the Comamonas and Morganella genera, have been shown to occasionally cause infection in immunocompromised individuals. , …”
Section: Resultsmentioning
confidence: 61%
“…followed by unclassified members of Xanthomonadales, Dokdonella, Pseudomonas, and Hydrogenophilales. Although many of the potential mcr- 5 host identified in this study have not been associated with this variant, it has been observed in Stenotrophomonas isolated from poultry farm waste and Cupriavidus isolated from a clinical case and well water. , Both Stenotrophomonas and Cupriavidus genera contain species that are considered emerging global pathogens while others, such as species within the Comamonas and Morganella genera, have been shown to occasionally cause infection in immunocompromised individuals. , …”
Section: Resultsmentioning
confidence: 61%
“…However, the mobile colistin resistance mechanism was also detected via the isolation of one mcr-5 -producing Cupriavidus gilardii strain from the well water of the maternity hospital. The whole genome of this strain was sequenced and has already been published [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, colistin-resistant enterobacteria isolated from tap water was potentially related to mutational mechanisms. In addition, we reported the first mcr-5 positive Cupriavidus gilardii through its isolation from well water [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 There are currently no recommendations for antimicrobial use to treat C. gilardii infections. 8 Moreover, the high case fatality rate of C. gilardii infections may be related to the characteristics of acquired drug resistance. 8 , 10 Compared with other clinically well-known pathogens, we know very little about the genome, clinical characteristics, and therapy of C. gilardii .…”
Section: Introductionmentioning
confidence: 99%